Analysis of Several Factors Influencing the Level of Community Welfare in Bangkalan Regency - Mareta Aurellya Yusnika; Kiky Asmara (Lembaga Riset dan Inovasi Al-Matani, 2023)
The level of community welfare in Bangkalan Regency shows poor conditions, as evidenced by the HDI ranking in the 2nd lowest position in the province of East Java. This shows the need for improvement. This study aims to identify and analyze the factors that influence the level of community welfare in Bangkalan Regency. The study uses the variables Gross Regional Domestic Product, District Minimum Wage, and Open Unemployment Rate. It uses secondary data from time series data for ten years (2012 until 2022) obtained from the BPS Office of East Java Province and the BPS Regency of Bangkalan. The analysis tool used is multiple linear regression using E-Views 12 software. The study results show that the Gross Regional Domestic Product has a negative and no significant effect on the level of community welfare in Bangkalan Regency. The District Minimum Wage has a positive and considerable influence on the level of community welfare in Bangkalan Regency. The open Unemployment Rate has a positive and insignificant effect on the level of community welfare in Bangkalan Regency.